Ecopiling: a combined phytoremediation and passive biopiling system for remediating hydrocarbon impacted soils at field scale - Germaine, Kieran J.; Byrne, John; Liu, Xuemei; Keohane, Jer; Culhane, John; Lally, Richard D.; Kiwanuka, Samuel; Ryan, David; Dowling, David N. (Frontiers in Plant Science, 2015)
Biopiling is an ex situ bioremediation technology that has been extensively used for remediating a wide range of petrochemical contaminants in soils. Biopiling involves the assembling of contaminated soils into piles and stimulating the biodegrading activity of microbial populations by creating near optimum growth conditions. Phytoremediation is another very successful bioremediation technique and involves the use of plants and their associated microbiomes to degrade, sequester or bio-accumulate pollutants from contaminated soil and water. The objective of this study was to investigate the effectiveness of a combined phytoremediation/biopiling system, termed Ecopiling, to remediate hydrocarbon impacted industrial soil. The large scale project was carried out on a sandy loam, petroleum impacted soil (1613 mg Total Petroleum Hydrocarbons (TPH) kg-1 soil). The contaminated soil was amended with chemical fertilisers, inoculated with TPH degrading bacterial consortia and then used to construct passive biopiles. Finally, a phyto-cap of perennial rye grass (Lolium multiflorum) and white clover (Trifolium repens) was sown on the soil surface to complete the Ecopile. Monitoring of important physico-chemical parameters was carried out at regular intervals throughout the trial. Two years after construction the TPH levels in the petroleum impacted Ecopiles were below detectable limits in all but 1 subsample (152mg TPH kg-1 soil). The Ecopile system is a multi-factorial bioremediation process involving bio-stimulation, bio-augmentation and phytoremediation. One of the key advantages to this system is the reduced costs of the remediation process, as once constructed, there is little additional cost in terms of labour and maintenance (although the longer process time may incur additional monitoring costs). The other major advantage is that many ecological functions are rapidly restored to the site and the process is aesthetically pleasing.